2004
DOI: 10.1111/j.1525-1314.2004.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverted metamorphic sequence in the Sikkim Himalayas: crystallization history, P–T gradient and implications

Abstract: The metapelitic rocks of the Sikkim Himalayas show an inverted metamorphic sequence (IMS) of the complete Barrovian zones from chlorite to sillimanite + K-feldspar, with the higher grade rocks appearing at progressively higher structural levels. Within the IMS, four groups of major planar structures, S 1 , S 2 and S 3 were recognised. The S 2 structures are pervasive throughout the Barrovian sequence, and are sub-parallel to the metamorphic isograds. The mineral growth in all zones is dominantly syn-S 2 . The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(99 citation statements)
references
References 48 publications
5
94
0
Order By: Relevance
“…Available studies indicated that metamorphic rocks from the HHCS and the NHGD had experienced metamorphic reactions at pressure greater than 800 MPa, and temperature up to 800℃ [33][34][35] . Partial melting of amphibolite can occur at these conditions [36] .…”
Section: Mechanism For the Formation Of The Yardoi Leucogranitementioning
confidence: 99%
“…Available studies indicated that metamorphic rocks from the HHCS and the NHGD had experienced metamorphic reactions at pressure greater than 800 MPa, and temperature up to 800℃ [33][34][35] . Partial melting of amphibolite can occur at these conditions [36] .…”
Section: Mechanism For the Formation Of The Yardoi Leucogranitementioning
confidence: 99%
“…One of the most well-known discontinuities is the Main Central Thrust (MCT) which separates the Higher Himalayan Sequence in the north from the underlying Lesser Himalayan Sequence in the south. The Higher Himalayan Crystalline Sequence (HHCS) consists of quartzofeldspathic gneisses of both igneous and sedimentary parentage that suffered high-grade amphibolite and granulite facies metamorphism (Neogi et al 1998;Catlos et al 2001;Dasgupta et al 2004). In the Darjeeling-Sikkim area, the base of the HHCS is represented by a strongly deformed granitic body called the Lingtse Gneiss (Acharyya 1978).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Studies have variously bounded the Main Central Thrust zone with two named thrusts (Catlos et al 2004;Dubey et al 2005;Bhattacharyya & Mitra 2009, placed the Main Central Thrust at the top of the Main Central Thrust zone (Ghosh 1956;Acharyya 1975;Banerjee et al 1983) or placed the Main Central Thrust at the base of the Main Central Thrust zone (Searle & Szulc 2005). Furthermore, the distinctive Palaeoproterozoic Lingtse gneiss, strongly sheared along the Main Central Thrust zone throughout the Sikkim Himalaya, has been used in other studies as a defining lithology for determining the location of the Main Central Thrust (Neogi et al 1998;Chakraborty et al 2003;Dasgupta et al 2004).…”
Section: Geological Settingmentioning
confidence: 99%